The excavation of WWII RAF bomber, Halifax LV881-ZA-V*. Issue 1 (2nd January 2017) - Marter, Phil; Visser, Ronald; Alders, Pim; Röder, Christoph; Gottwald, Michael; Mank, Mirko; Hubbard, Steven; Recker, Udo
Abstract: This article outlines the preliminary results of archaeological fieldwork at the crash site of RAF Halifax bomber LV881-ZA-V and explores some of the challenges presented by the excavation of this military wartime crash site. The aircraft and her crew were shot down by a German night fighter in the early hours of 31 March 1944 during the infamous Nuremberg Raid. Four of her crew were killed and the remaining three were taken prisoner and later took part in the 'Long March'. All three survived the war. An international team comprised of staff and students from Germany, the Netherlands, Finland and the UK explored what remained of the crash site, located on a hill outside the village of Steinheim, north east of Frankfurt in the German Federal State of Hesse.